Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Get detailed and accurate answers to your questions from a community of experts on our comprehensive Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Let's solve the problem by calculating the values of [tex]\( y \)[/tex] for specific values of [tex]\( x \)[/tex] and filling in the missing entries in the table.
Given the function:
[tex]\[ y = x^2 - 3x - 2 \][/tex]
We need to find the values for [tex]\( y \)[/tex] when [tex]\( x = -1 \)[/tex], [tex]\( x = 0 \)[/tex], and [tex]\( x = 3 \)[/tex], represented as [tex]\( A \)[/tex], [tex]\( B \)[/tex], and [tex]\( C \)[/tex] respectively.
1. Calculate [tex]\( y \)[/tex] when [tex]\( x = -1 \)[/tex] (this is [tex]\( A \)[/tex]):
[tex]\[ A = (-1)^2 - 3(-1) - 2 \][/tex]
[tex]\[ A = 1 + 3 - 2 \][/tex]
[tex]\[ A = 2 \][/tex]
2. Calculate [tex]\( y \)[/tex] when [tex]\( x = 0 \)[/tex] (this is [tex]\( B \)[/tex]):
[tex]\[ B = (0)^2 - 3(0) - 2 \][/tex]
[tex]\[ B = 0 - 0 - 2 \][/tex]
[tex]\[ B = -2 \][/tex]
3. Calculate [tex]\( y \)[/tex] when [tex]\( x = 3 \)[/tex] (this is [tex]\( C \)[/tex]):
[tex]\[ C = (3)^2 - 3(3) - 2 \][/tex]
[tex]\[ C = 9 - 9 - 2 \][/tex]
[tex]\[ C = -2 \][/tex]
So, the correct values to replace [tex]\( A \)[/tex], [tex]\( B \)[/tex], and [tex]\( C \)[/tex] in the table are:
[tex]\[ A = 2, \ B = -2, \ C = -2 \][/tex]
The completed table should be:
[tex]\[ \begin{tabular}{c||c|c|c|c|c} $x$ & -1 & 0 & 1 & 2 & 3 \\ \hline $y$ & 2 & -2 & -4 & -4 & -2 \\ \end{tabular} \][/tex]
Given the function:
[tex]\[ y = x^2 - 3x - 2 \][/tex]
We need to find the values for [tex]\( y \)[/tex] when [tex]\( x = -1 \)[/tex], [tex]\( x = 0 \)[/tex], and [tex]\( x = 3 \)[/tex], represented as [tex]\( A \)[/tex], [tex]\( B \)[/tex], and [tex]\( C \)[/tex] respectively.
1. Calculate [tex]\( y \)[/tex] when [tex]\( x = -1 \)[/tex] (this is [tex]\( A \)[/tex]):
[tex]\[ A = (-1)^2 - 3(-1) - 2 \][/tex]
[tex]\[ A = 1 + 3 - 2 \][/tex]
[tex]\[ A = 2 \][/tex]
2. Calculate [tex]\( y \)[/tex] when [tex]\( x = 0 \)[/tex] (this is [tex]\( B \)[/tex]):
[tex]\[ B = (0)^2 - 3(0) - 2 \][/tex]
[tex]\[ B = 0 - 0 - 2 \][/tex]
[tex]\[ B = -2 \][/tex]
3. Calculate [tex]\( y \)[/tex] when [tex]\( x = 3 \)[/tex] (this is [tex]\( C \)[/tex]):
[tex]\[ C = (3)^2 - 3(3) - 2 \][/tex]
[tex]\[ C = 9 - 9 - 2 \][/tex]
[tex]\[ C = -2 \][/tex]
So, the correct values to replace [tex]\( A \)[/tex], [tex]\( B \)[/tex], and [tex]\( C \)[/tex] in the table are:
[tex]\[ A = 2, \ B = -2, \ C = -2 \][/tex]
The completed table should be:
[tex]\[ \begin{tabular}{c||c|c|c|c|c} $x$ & -1 & 0 & 1 & 2 & 3 \\ \hline $y$ & 2 & -2 & -4 & -4 & -2 \\ \end{tabular} \][/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.